Human Mesenchymal Stem Cells Seeded on the Natural Membrane to Neurospheres for Cholinergic-like Neurons - Priscila Elias Ferreira Stricker; Daiany de Souza Dobuchak; Ana Carolina Irioda; Bassam Felipe Mogharbel; Celia Regina Cavichiolo Franco; José Roberto de Souza Almeida Leite; Alyne Rodrigues de Araújo; Felipe Azevedo Borges; Rondinelli Donizetti Herculano; Carlos Frederico de Oliveira Graeff; Juan Carlos Chachques; Katherine Athayde Teixeira de Carvalho (Membranes, 2021)
This study aimed to differentiate human mesenchymal stem cells (hMSCs) from the human umbilical cord in cholinergic-like neurons using a natural membrane. The isolation of hMSCs from Wharton’s jelly (WJ) was carried out using “explant” and mononuclear cells by the density gradient from umbilical blood and characterized by flow cytometry. hMSCs were seeded in a natural functional biopolymer membrane to produce neurospheres. RT-PCR was performed on hMSCs and neurospheres derived from the umbilical cord. Neural precursor cells were subjected to a standard cholinergic-like neuron differentiation protocol. Dissociated neurospheres, neural precursor cells, and cholinergic-like neurons were characterized by immunocytochemistry. hMSCs were CD73+, CD90+, CD105+, CD34- and CD45- and demonstrated the trilineage differentiation. Neurospheres and their isolated cells were nestin-positive and expressed NESTIN, MAP2, ßIII-TUBULIN, GFAP genes. Neural precursor cells that were differentiated in cholinergic-like neurons expressed ßIII-TUBULIN protein and choline acetyltransferase enzyme. hMSCs seeded on the natural membrane can differentiate into neurospheres, obtaining neural precursor cells without growth factors or gene transfection before cholinergic phenotype differentiation.